2001
DOI: 10.1007/s002130000584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MK-801 and nicotine combinations on memory consolidation in CD1 mice

Abstract: In conclusion, from the present research, it is evident that NMDA glutamate and nicotinic acetylcholine receptor systems interact in modulating memory consolidation in CD I mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…We observed that tacrine and rivastigmine were also effective against the dizocilpine-induced learning impairments, in agreement with Csernansky's hypothesis. Moreover, the observation that direct application of nicotine alleviated the dizocilpine-induced learning deficits (Ciamei et al, 2001) is in line with such hypothesis.…”
Section: Discussionsupporting
confidence: 64%
“…We observed that tacrine and rivastigmine were also effective against the dizocilpine-induced learning impairments, in agreement with Csernansky's hypothesis. Moreover, the observation that direct application of nicotine alleviated the dizocilpine-induced learning deficits (Ciamei et al, 2001) is in line with such hypothesis.…”
Section: Discussionsupporting
confidence: 64%
“…Various paradigms have been developed to assess similar learning and memory, and attention functions in rodents and similar to what is seen in humans, nicotine has been shown to improve rodent deficits in these paradigms [105,106,107,108,109]. DMXBA improves monkey performance on a delayed matching to sample task, an effect that persists for 24 hours after drug administration [110].…”
Section: Dmxba As a Prototype Drugmentioning
confidence: 99%
“…Nicotinic acetylcholine receptor (nAChR) agonists are among several classes of cognitiveenhancing agents under investigation for treatment of cognitive deficits associated with schizophrenia (Levin and Rezvani 2002). Nicotine improves memory in animals (Arendash et al 1995;Ciamei et al 2001;Levin and Simon 1998) and improves attention, learning, and memory in healthy adults (Ernst et al 2001;Lawrence et al 2002;Mancuso et al 1999;McClernon et al 2003;Rusted et al 1998;Rusted et al 2005;Levin et al 2006). In addition, nicotine has demonstrated benefits in these domains in patients with Alzheimer's disease (Wilson et al 1995), age-associated memory impairment (White and Levin 2004), attention deficit hyperactivity disorder (Poltavski and Petros 2006), and depression .…”
Section: Introductionmentioning
confidence: 98%